Liberia : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2007)
Liberia's Interim Poverty Reduction Strategy (iPRS) sets out the emerging process and framework for recovery and reconstruction in the context of post-conflict Liberia. The iPRSP sets out the national socio-economic context, the preparatory process, dimensions of the emerging policy, capacity-building and program choices and priorities for poverty reduction and development, as well as anticipated implementation challenges. It also represents a further opportunity for deepening Liberia's development partnership. Liberia needs to be rebuilt at all levels of the public sector, private sector, and civil society.